Factors associated with adherence to guidelines of good clinical practice during hospital treatment of patients with the first episode of schizophrenia spectrum disorders - Stašević, Milena; Stasevic - Karlicic, Ivana; Divac, Nevena; Grgurević, Anita; Grbić, Igor (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Adherence to the guidelines of Good Clinical Practice (GCP) during the treatment of specific disorders is considered a guarantee of the implementation of a uniform, evidence-based clinical practice in psychiatry. The aim of this study was to analyze the concordance of prescribing patterns of antipsychotic drugs with the recommendations of good clinical practice in Serbia and an insight into the effects that introduction of the National Guideline for the Diagnosis and Treatment of Schizophrenia had on the prescribing practice in this area. Methods. Non-interventional, observational study was conducted at the Clinic for Mental Disorders “Dr Laza Lazarević” in Belgrade. It included a consecutive sample of 675 previously untreated patients, hospitalized from January 1st, 2012 to December 31st, 2015, dismissed with a discharge diagnosis of any of schizophrenia spectrum disorders. The data about demographic and clinical characteristics of patients, characteristics of prescribers and prescribed antipsychotics were obtained retrospectively, from the patients’ medical records. For the analysis of primary data, the descriptive statistical methods and methods for testing statistical hypotheses were used. A method of logistic regression was used to identify the factors associated with adherence to the GCP recommendations. Results. Totaly, 446 (66.1%) of subjects were treated with antipsychotic monotherapy. After the introduction of National Guideline for the Diagnosis and Treatment of Schizophrenia prescribing of second generation antipsychotic monotherapy (78.41% vs. 63.5%, respectively; p < 0.001) increased significantly compared to the previous period. The factors independently associated with adherence to the recommendations of the GCP were the year of hospitalization, the age of the prescriber, and the age and education of the patient. Conclusion. After the introduction of the National Guide to Good Clinical Practice for the Diagnosis and Treatment of Schizophrenia there have been significant, but insufficient changes in the prescribing patterns of antipsychotics during the treatment of the first psychotic episode in Serbia.
Keywords: practice guidelines as topic; guideline; serbia; schizophrenia; drug therapy; antipsychotic agents